Industrial Change in the Bangkok Urban Region - Thailand Office of the National Economic and Social Development Board; World Bank (World Bank, Washington, DC, 2017)
The 2009 World Development Report (WDR) on economic geography aroused interest among policymakers in Thailand and led to an agreement between the Office of the National Economic and Social Development Board (NESDB) and the East Asia Poverty Reduction and Economic Management Unit of the World Bank to collaborate on a study of the Bangkok urban region which is Thailand's engine of growth. This report is the fruit of continuous collaboration between the NESDB and the World Bank. This report was prepared by a joint NESDB-World Bank team. For over three decades, Thailand has consistently ranked as one of the fastest growing Southeast Asian economies. This growth performance is principally the result of high levels of domestic and foreign investment that enabled Thailand to build a diversified, export oriented industrial economy and absorb technologies from more advanced countries. Much of this industrialization has been concentrated in Bangkok and five adjacent provinces that comprise the Bangkok metropolitan region and, in recent years, a few provinces further to the south east which are now a part of the Bangkok urban region. The principal economic challenge for Thailand is to enhance the industrial potential of the region so as to sustain real Gross Domestic Product (GDP) growth at between five and six percent per annum. This is well below the growth rates of eight and nine percent per annum achieved during 1985-1995. Bangkok must ensure that public amenities, services, housing and transport infrastructures receive sustained attention and financing. The quality of life will be vital to retaining a large talent pool, attracting investment and sustaining the tourist industry.